Analysis And Redesigning Of Key Result Areas (kras) For A Private Company With Special Reference To Extinct Fire Engineers Private Limited At Mumbai - Jain, Arjita (Gyan Management Journal, 2020)
Key Result Areas (KRAs) refer to general areas of outcomes for which a role, or a combination of roles, is  responsible. These are the areas within the organization where an individual/group, is responsible for  the  results. As Extinct Fire was undergoing the organizational  restructuring process, there was a  strong need for redesigning Job Descriptions and the KRAs. Researcher was engaged in redesigning the  KRAs various levels at length. The data was collected internally from variousdepartments by scanning  old  KRA  documents;  which  were  discussed  with  department  wise  individual  team  membersand  approved by respective Head of the Department and sanctioned by Managing Director. The Standard  Operating Procedureswere made after the collection of the information by meeting and discussion held  with departmental head. New KRAs were finalized; entire redesigning process was carried out under  the guidance of head HR.  The Redesigning of KRAs was carried out in 13 Departments: Enterprise  Resource Planning (ERP) Department, Maintenance Contract (AMC) Department, Information and  Technology Department, Design Department, Purchase Department, Planning & MIS Department,  Human  Resource  Department,  Marketing  Department,  Accounts  &  Finance  Department,  Projects  Department, Estimation Department, Contracts Department, and for total 263 (Departments + Site  Staff) positions KRA Redesigning was carried out. This paper presents the working of few selected  departments.
Keywords: Key Result Areas; Performance Management; Skill Assessment; Performance Appraisal; Organizational Development